Mineralization age and genesis of the makeng-style iron deposits in the Paleo-Pacific tectonic domain of South China: In situ LA-ICPMS garnet U-Pb chronological and geochemical constraints - Wang, Sen; Cao, Ke; Zhang, Da; Yi, Jin-Jun; Hu, Bo-Jie; Yang, Jing; Cai, Meng-Ying; Zhang, Yao-Yao; Yuan, Yuan; Pan, Tian-Wang (Frontiers in Earth Science, 2023)
To reveal the genesis of Makeng-style iron polymetallic deposits from SE China in the paleo-Pacific tectonic domain, a new analytical method of LA-ICPMS garnet U‒Pb dating and rare earth element analysis was conducted for the Makeng, Luoyang, Dapai and Pantian deposits. The U‒Pb dating results of 9 garnet skarn samples from these deposits suggested that the Makeng-style iron polymetallic deposits mainly formed during 137-130 Ma, which is consistent with the zircon U‒Pb and molybdenite Re‒Os ages. This study provides more direct evidence of the mineralization age and the relationship between mineralization and granite, compared with previous studies on the zircon U‒Pb dating for granites in the ore fields. Rare earth element (REE) analysis results and REE patterns of 4 representative garnet samples from the Makeng, Luoyang, Dapai and Pantian deposits show that they are similar to typical skarn deposits, but obvious differences in the REE distribution types indicate that the ore-forming process may be distinct due to different mineralizing fluid for these Makeng-style deposits. Our new garnet U‒Pb dating and rare earth element analysis result not only provides new evidence for the mineralization age and genesis of the Makeng-style deposits but is also of great significance to promote the application of U‒Pb dating methods to research skarn type deposits.